2017
DOI: 10.1245/s10434-017-5899-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Grade in Neuroendocrine Tumor Metastases Negatively Impacts Survival

Abstract: Background Tumor grade is an important predictor of survival in gastroenteropancreatic (GEP) neuroendocrine tumors (NETs), as determined by Ki-67 expression and mitotic rate. NETs generally grow indolently, but some cells may acquire traits facilitating metastasis. It is unclear how frequently metastases differ in grade from their primary tumors, and whether increasing grade in metastases affects prognosis. Methods Ki-67 immunohistochemistry was performed on resected GEPNET specimens and cases with results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 27 publications
4
52
0
1
Order By: Relevance
“…Gracia P et al [5] reported that the Ki-67 was higher in the metastatic lesion than in the primary lesion in dogs [5]. There are some variations, increasing (24%), stable (66%), and decreasing (10%) of Ki-67 in metastatic lesion in human neuroendocrine tumors [7]. Since Ki-67 can be used for grading or predicting prognosis in human PNSTs [18][19][20] and in canine PNSTs [15], Ki-67 is an available marker for physiological states and prognosis in MPNSTs.…”
mentioning
confidence: 99%
“…Gracia P et al [5] reported that the Ki-67 was higher in the metastatic lesion than in the primary lesion in dogs [5]. There are some variations, increasing (24%), stable (66%), and decreasing (10%) of Ki-67 in metastatic lesion in human neuroendocrine tumors [7]. Since Ki-67 can be used for grading or predicting prognosis in human PNSTs [18][19][20] and in canine PNSTs [15], Ki-67 is an available marker for physiological states and prognosis in MPNSTs.…”
mentioning
confidence: 99%
“…Grillo et al found 39% discrepancy in grade between primary and metastatic tumors [33]. Keck KJ et al found grade variation occurred in 34% of patients between primary and metastatic tumors [34]. In our study, we found that, in 54.3% of GEP-NENs patients, the Ki-67 index differed between primary and metastatic lesions; as a result, the WHO classification changed in 8.6% of the patients.…”
Section: Discussionmentioning
confidence: 40%
“…13 The tumor grade was assigned according to the World Health Organization 2010 classification of tumors of the digestive system based on the Ki-67 index and mitotic rate. 14 For patients in whom the Ki-67 index was calculated in both the primary tumor and metastases, the greater value was used to determine overall grade based on the findings of Keck et al 15…”
Section: Methodsmentioning
confidence: 99%